BIJAK BERMEDIA SOSIAL: IMPLEMENTASI LITERASI DIGITAL DI KALANGAN PELAJAR - Fajri, Chotamul; Audy Febriyana; Natasya Febianty; Shelika Nur Aisah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The rapid development of digital technology has made social media and the internet an integral part of students' lives. However, the high intensity of digital media use also carries various risks, one of which is cyberbullying, which can affect students' mental health and motivation to learn. Therefore, efforts to improve digital literacy are needed so that students are able to use social media wisely, safely, and responsibly. This Community Service Activity (PKM) aims to increase students' understanding and awareness of digital literacy, particularly related to cyberbullying, its impact on mental health and learning motivation, as well as prevention and handling efforts. The activity was carried out face-to-face at Muhammadiyah 25 Pamulang High School, involving 35 students as participants. The methods used included peer-to-peer training, material delivery, question and answer sessions, experience sharing, interactive discussions, and ice breaking. The results of the activity showed that students gained a better understanding of the various forms of cyberbullying, its negative impacts, and the importance of maintaining ethics and mutual respect in social media. In addition, students also showed an increased awareness of the importance of creating a healthy digital environment that supports the learning process. Thus, this PKM activity made a positive contribution to shaping wise, responsible, and ethical attitudes among students in using social media and the internet.